The impact of harmonious and obsessive passion on entrepreneurial self-efficacy and curiosity: The evidence from housewives in Banyumas regency - Achmad Sudjadi; Devani Laksmi Indyastuti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
There has been a limited amount of research conducted on the specific outcomes associated with harmonious and obsessive passion. Therefore, this study aims to fill the gap by examining the effects of harmonious and obsessive passions on entrepreneurial self-efficacy and curiosity. Distinctions between the impacts of harmonious and obsessive passions are established, setting it apart from previous studies. The results show that harmonious passion positively impacts entrepreneurial self-efficacy, whereas obsessive passion lacks such an effect. However, both types of passion positively influence entrepreneurial curiosity. The sample consists of 236 housewives from Banyumas Regency, selected through convenience sampling. Moreover, this study suggests that harmonious passion yields more beneficial outcomes than obsessive passion. Practical applications of the results include fostering entrepreneurial self-efficacy in housewives by enhancing harmonious passion through internalization processes. These processes can be facilitated through entrepreneurial-focused interventions, such as training programs, educational modules, and participation in entrepreneurial events.